Adaptation of land use based on the assessment of inundation risk in the Kapos Valley, Southwest Hungary - Gyenizse, Péter; Lóczy, Dénes; Dezső, József; Pirkhoffer, Ervin; Słowik, Marcin (Hungarian Geographical Bulletin, 2020)
Complex river rehabilitation/restoration projects devote equal attention to the improvement of hydromorphological conditions and the neighbouring floodplain environment. Since land use exerts a heavy control on the hydrological cycle of floodplains, land use optimization is a central task in floodplain rehabilitation. In floodplains where large surfaces are temporarily inundated, the optimal allocation of land use classes involves the preservation of wetlands, maintenance of grasslands (meadows and pastures) and forests, and the restriction of arable land to higher ground with the lowest inundation hazard. The detailed mapping of land use against the distribution of soil types and fluvial landforms provides a solid basis for land use optimization. Rehabilitation design is presented in the paper on the example of the Kapos Valley, where inundations in the wet year of 2010 caused great damage to agricultural crops and efforts are directed to better water management (excess water reduction and floodwater retention) on the floodplain. Land use conversions, which are less expensive and easier to implement, are preferred to structural (engineering) solutions.